Bioabsorbable plating in the treatment of pediatric clavicle fractures: A biomechanical and clinical analysis. (June 2018) - Osborn, Emily J.; Farnsworth, Christine L.; Doan, Joshua D.; Edmonds, Eric W.
Abstract: Background: Classic implants for operative intervention of mid-shaft clavicle fractures in adolescents can become symptomatic, requiring removal. This study compares 1) biomechanical properties and 2) clinical outcomes in adolescents of mid-shaft clavicle fracture fixation with bioabsorbable versus metal implants. Methods: Six synthetic clavicles with mid-shaft fractures underwent bioabsorbable plating. A testing frame applied 10 non-destructive torsion and 10 axial compression cycles, followed by cantilever bending to failure. Stiffness was calculated; maximum failure load and failure mode were recorded. Results were compared to previous data for locked metal constructs. Retrospective review of surgically treated clavicle fractures over three years included functional and radiographic outcomes. Findings: Bioabsorbable plates had lower torsional stiffness ( P  < 0.001) and maximum cantilever load ( P  < 0.0001) than locked metal plates. There was no significant difference in compression stiffness ( P  = 0.2) or cantilever bending stiffness ( P  = 0.4). Primary failure of metal plates was screw pull-out compared to plate bending in bioabsorbable constructs. Seven patients with bioabsorbable implants were included. All patients with bioabsorbable constructs achieved radiographic union, but 71% lost reduction. Despite fracture angulation, all achieved normal shoulder function after one year determined by QuickDASH evaluation. None required a second surgery. Interpretation: Bioabsorbable implants had lower torsional stiffness and cantilever failure load, but comparable compression stiffness to metal implants. Bioabsorbable implants failed via gradual bending versus the catastrophic failure seen in metal implants. The clinical review allows understanding of the sequelae of this lower failure load of bioabsorbable plates where their use allowed in fracture displacement, yet achievement of ultimate radiographic union and acceptable functional outcomes. Highlights: Adolescent midshaft clavicle fractures are fixed with metal or bioabsorble plates. Bioabsorbable plates deform plastically, with inferior stiffness. Metal plates required removal (13%) but bioabsorbable plates did not. All bioabsorbable plated fractures healed, with risk of lost radiographic reduction. Bioabsorbable plating outcomes were excellent for midshaft clavicle fractures.